Modern hip fracture care still involves nearly 3 days of bed rest – findings of the national Physiotherapy 'Hip Sprint' Audit in 2017. (2019) - Fagan, Elizabeth; Hannaford, James; Liddicoat, Meghan; Hove, Ruth ten; Johansen, Antony
No abstract available